Classification and research progress of implant surface antimicrobial techniques - Tian-Xia Zheng; Wen Li; Ying-Ying Gu; Di Zhao; Meng-Chun Qi (Elsevier, 2022)
Due to the good biocompatibility and ideal mechanical property, titanium implants have been widely used in dental clinic and orthopedic surgery. However, bacteria induced infection can cause per-implant inflammation and decrease the success rate of implant surgery. Therefore, developing antimicrobial techniques is essential to successful application of titanium implants. Many surface antimicrobial techniques, including antimicrobial coating and surface modifications, have been explored and they always exert antimicrobial effect by reducing bacterial adhesion, inhibiting their metabolism, or destructing cell structure. In this paper, different surface antimicrobial techniques and their recent research progress are reviewed to provide a brief insight on this area.